(untitled) (Journal of the College of Basic Education, 2026)
The educational process seeks to improve students’ academic achievement, particularly in subjects of a philosophical and aesthetic nature that require deep understanding and analysis of concepts. The present study aimed to identify the effectiveness of the M.U.R.D.E.R strategy in enhancing the achievement of students in the Art Education Department in the subject of Aesthetics. The researcher adopted an experimental methodology using a pretest–posttest design with two equivalent groups (experimental and control). The research population consisted of third-year students from the Colleges of Basic Education at Al-Mustansiriyah University and the University of Maysan. The research sample included (62) male and female students from the College of Basic Education at Al-Mustansiriyah University, who were randomly assigned into two equivalent groups. The experimental group was taught according to the M.U.R.D.E.R strategy, while the control group was taught using the conventional method. An achievement test of the multiple-choice type was used, consisting of (30) items in its final form. The results revealed statistically significant differences at the (0.05) level between the experimental and control groups in the post-achievement test, as well as significant differences between the pre- and post-tests for the experimental group, all in favor of the experimental group. Moreover, the adjusted gain ratio based on McGuigan’s equation indicated a noticeable improvement in students’ academic achievement, demonstrating the effectiveness of the M.U.R.D.E.R strategy in enhancing the achievement of Art Education Department students in the subject of Aesthetics